Proceedings of the 6th ACM/IEEE Symposium on Architectures for Networking and Communications Systems 2010
DOI: 10.1145/1872007.1872053
|View full text |Cite
|
Sign up to set email alerts
|

The case for hardware transactional memory in software packet processing

Abstract: Software packet processing is becoming more important to enable differentiated and rapidly-evolving network services. With increasing numbers of programmable processor and accelerator cores per network node, it is a challenge to support sharing and synchronization across them in a way that is scalable and easy-to-program. In this paper, we focus on parallel/threaded applications that have irregular control-flow and frequently-updated shared state that must be synchronized across threads. However, conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Several other works targeted the implementation of HTM for field programmable gate array (FPGA) platform. ATLAS [14], Real Time Transactional Memory (RTTM) [15] and NetTM [9] were all hardware implementations that were built based on fixed configurations. Their performance are highly dependent on running applications.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other works targeted the implementation of HTM for field programmable gate array (FPGA) platform. ATLAS [14], Real Time Transactional Memory (RTTM) [15] and NetTM [9] were all hardware implementations that were built based on fixed configurations. Their performance are highly dependent on running applications.…”
Section: Related Workmentioning
confidence: 99%
“…Various architectures proposed by [5,8,9,16] can be categorized into two main aspects: Version Management and Conflict Management [7]. Fig.…”
Section: A Htm Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Many previously reported methods mainly focus on improving the rule matching algorithms, and/or using FPGA [1], [2] or GPU [3]- [6] for efficient content-matching, and the results show that the ratio of running time used for matching is decreasing with the enhancement of matching performance. Experiments from some other researchers [7] further indicated that when the ratio of the matching time to the overall decrease to 1%, Stream4 (which reassembles streams in previous Snort version) will take on the load of 80% when it is used to assemble the packets.…”
Section: Introduction Dpi (Deep Packet Inspection) Is a Critical Tmentioning
confidence: 99%